Ethical Climate’s Mediating Role on the Relationship Between Emotional Intelligence and Job Satisfaction - Pekkan Nazmiye Ulku; Bicer Mehmet (Central European Management Journal, 2022)
Purpose: The purpose of this article is to determine the effects of emotional intelligence (EI) on job satisfaction and to examine whether ethical climate has a mediating role in this effect.